Air-dried porous powder of polymethyl methacrylate modified cellulose nanocrystal nanocomposite and its diverse applications. (1st March 2020) - Liu, Yunxiao; Zhou, Lijuan; Wang, Li; Pan, Xiaolong; Wang, Kuntao; Shu, Jie; Liu, Lehuan; Zhang, Hui; Lin, Leyu; Shi, Xinyan; Schlarb, Alois K.; Zhang, Jianming
Abstract: Owing to the advantages in storage, transportation and melt-processing, the powder form of cellulose nanocrystals (CNCs) as an attractive biomass filler is highly desired for the industrial application. Herein, by systematically tailoring the reaction conditions, we prepared the air-dried porous powder of CNCs modified with PMMA (CNCs-g-PMMA) via a green synthesis route, that is, using ceric ammonium nitrate (CAN) as an initiator in aqueous medium. Our results show that the porous powder of air-dried CNCs-g-PMMA can be easily obtained when the grafting ratio of PMMA was higher than 70 wt%. CNCs-g-PMMA porous powder demonstrates high specific surface area (47.8 m 2 /g), excellent hydrophobicity and oleophilicity properties. It therefore can be used as a filter for oil/water separation or as a highly efficient absorbing material. Moreover, benefiting from the improved thermal stability of CNCs and melt-processing character of PMMA, the porous powder of CNCs-g-PMMA has been converted to a transparent film by a simple compression molding. The as-prepared film demonstrates extraordinary UV shielding and mechanical stability upon heating. Particularly, there is an extraordinary increase in glass transition temperature of PMMA from 112.6 to 138.6 °C. This research provides a facile and green strategy to fabricate CNCs-g-PMMA porous powder, which shows industrial applications from different perspectives. Graphical abstract: Image 1